Direct Wafer Bonding of GaN for Power Devices Applications. (20th July 2018) - Dragoi, Viorel; Razek, Nasser; Guiot, Eric; Caulmilone, Raphael; Liao, Michael; Wang, Yekan Steven; Goorsky, Mark S.; Yates, Luke; Graham, Samuel
Abstract : Over the past decade the interest in gallium nitride – based electronic applications increased significantly. The economical advantages of GaN-based applications imposed the development of new manufacturing technologies. Among them, wafer bonding process solutions could be further developed and optimized for the manufacturing of GaN engineered substrates. The most significant benefit of using wafer bonding for GaN-based applications is the possibility to combine GaN with various substrate materials, offering a high flexibility by imposing strict quality requirements only to the surfaces of the substrates and not to their crystal structure.This work proposes two different process flows for "GaN-on-Something" substrates manufacturing. The features and benefits of the two process flows are illustrated by experimental results.